2021
DOI: 10.1111/trf.16656
|View full text |Cite
|
Sign up to set email alerts
|

X‐ and gamma‐irradiation have similar effects on the in vitro quality of stored red cell components

Abstract: Background: Blood components are irradiated to inactivate lymphocytes to prevent transfusion-associated graft versus host disease. As there are little data regarding the effects of X-irradiation on red blood cell components (RBCs), the in vitro quality of stored red cells (standard, pediatric, washed, and intrauterine transfusion [IUT]) following X-or gamma-irradiation was compared. Study design and methods: RBCs were pooled, split, and processed to produce standard (<14 days and < 5 days post-collection), ped… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 25 publications
5
7
0
Order By: Relevance
“…Moreover, at standard doses of irradiation for RCC there was no evidence of increased aggregation of proteins or membrane lipid peroxidation reported 28,29 . More recently, both gamma and x irradiation have been shown to cause an increase in microparticle formation in RCC, highly suggestive of membrane damage 30 . Altogether, the mechanism of increased permeability of cations across the RBC membrane post‐irradiation is unclear.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Moreover, at standard doses of irradiation for RCC there was no evidence of increased aggregation of proteins or membrane lipid peroxidation reported 28,29 . More recently, both gamma and x irradiation have been shown to cause an increase in microparticle formation in RCC, highly suggestive of membrane damage 30 . Altogether, the mechanism of increased permeability of cations across the RBC membrane post‐irradiation is unclear.…”
Section: Discussionmentioning
confidence: 97%
“…28,29 More recently, both gamma and x irradiation have been shown to cause an increase in microparticle formation in RCC, highly suggestive of membrane damage. 30 Altogether, the mechanism of increased permeability of cations across the RBC membrane post-irradiation is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…While this lends support to the Council of Europe/CSA and BCSH guidelines, we believe the in vitro red cell quality data presented herein provides no cause for concern in regard to the in vivo efficacy of units irradiated in accordance with AABB guidelines. It is imperative that the findings of this study be extrapolated to X‐ray irradiated RCCs given that several jurisdictions are beginning to implement this method as it does not rely on a radioactive source 26 . Marks et al recently indicated that there is a high degree of equivalency between the in vitro effects of X‐ray and gamma irradiation on stored RCCs, suggesting that irradiation timing and postirradiation storage durations could have a similar impact between both methods of irradiation 26 .…”
Section: Discussionmentioning
confidence: 98%
“…It is imperative that the findings of this study be extrapolated to X‐ray irradiated RCCs given that several jurisdictions are beginning to implement this method as it does not rely on a radioactive source 26 . Marks et al recently indicated that there is a high degree of equivalency between the in vitro effects of X‐ray and gamma irradiation on stored RCCs, suggesting that irradiation timing and postirradiation storage durations could have a similar impact between both methods of irradiation 26 . Nevertheless, it remains valuable to assess whether the stark increase in free Hb associated with an extended postirradiation storage duration can impact vascular function in vivo, particularly in animal models of sickle cell disease.…”
Section: Discussionmentioning
confidence: 99%
“…PRBC units may be irradiated to prevent graft-versus-host disease in high-risk recipient populations. In addition to increasing the hemolysis rate, both X and gamma irradiation may similarly increase sREV release [19][20][21]. The impact of the timing of irradiation is controversial.…”
Section: Influence Of Pretransfusion Processingmentioning
confidence: 99%